Study Of Electrical and Lighting Installations in Water Engineering Laboratory Buildings (Case Study: Laboratory of Water Engineering, University of Muhammadiyah Jember) - Noor Salim (Universitas Muhammadiyah Jember, 2022)
Electrical installation of buildings is an assembly of electrical equipment in buildings that are related to each other, to meet certain goals or purposes and have coordinated characteristics [2]. The design and installation of this electrical installation covers all aspects of the building, one of which is for the Water Engineering laboratory building. Electrical power in this laboratory building is used for room lighting, pumps, heating, cooling and so on. Based on the above, to obtain a water engineering laboratory building with optimal lighting, the use of durable pumps, the use of environmentally friendly cooling and heating devices and the selection of efficient and efficient tools for related purposes as well as the use of electricity that is efficient and safe. So it is necessary to study the Electrical and Lighting Installation in the Water Engineering Laboratory Building. From the results of this study, it can be concluded that for this laboratory lighting is used 20 TL lamps with each lamp 18 watts and uses lamps of 1350 lumens, laboratory operations use 2 pumps each with a power of 450 watts and heating and cooling equipment and tools the other has a power of 600 and for the distribution of electricity, 2 MCB panels are used, each of which is 6 amperes. It is recommended that each pump be made an individual panel so that safety in the experiment is not compromised when used together and there is a need for routine maintenance and control.